Pre-service teachers' reflection on their efficacy beliefs in conducting action research. Issue 2 (4th March 2022) - Ugalingan, Gina B.; Bautista, Aileen C.; Mante-Estacio, Ma. Joahna
ABSTRACT: This paper attempts to discuss Filipino pre-service teachers' reflections on their self-efficacy beliefs when they conduct action research as a culminating requirement for their degree. The study traces and identifies patterns to see possible consistencies or inconsistencies of the level of self-competence among the participants, as revealed by their self-reflections. This qualitative research involves 10 participants who were asked to write seven reflective journals each as they went through the various stages of doing action research. Using constant comparison, the researchers arrived at three themes guided by self-efficacy theory. Results reveal that previous performance accomplishments, perceptions toward the people they collaborated with, and their positive and negative emotions toward their various action research experiences are the sources of their self-efficacy beliefs. The results are worthy of being considered in improving the pre-service teaching curriculum, particularly the thesis component to which action research writing is included.